Paradigms Of Evaluation Of The Real Estate In Georgia, Such As Land And Forest - Sichinava, Alexander; Sekhniashvili, Dali; Chikava, Medea; Chikaidze, Nazi (European Scientific Journal, ESJ, 2016)
In the years following the land reform in Georgia and origination of private land property rights in the country, the formation of the land value started to be gradually regulated according to the market value prompted by the ‘demand-and-supply’ principle. In the authors’ opinion, the due management of the agricultural development of Georgia needs significant preparatory works. In the attempt to solve the existing problems, the article gives the situation analysis and certain recommendations. One of the reasons for the degradation of the eco-systems in Georgia and of forests in particular, is the failure to assess the eco-system service of forests, as the forest value is fixed by considering the opportunity to gain the timber and other secondary forest products only, without considering the environmental protection function of the forests. In some cases, the qualitative and quantitative parameters of the forest functions are assessed by using complex mathematical calculations, what in terms of scarce information, yield wrong assumptions. In addition, the methods of economic evaluation of the natural resources are sometimes contradictory. Therefore, the authors think that the concept of the gross economic value is best to use as the methodological approach in the economic evaluation. Value of natural capital or eco-system services in Georgia is not taken into account during the decision-making process either at a state, or a private level, or during the pricing of the forest profitability inter alia. In the article, the authors give their proposals regarding the optimal ways to solve these problems.